Composite antibacterial sweat-absorbing clothing fabric and process thereof
By mixing cotton pulp, graphene oxide solution, polyethylene, carbon nanotubes, silver-carrying antibacterial agent and moisture-permeable hot melt adhesive in a certain proportion, electrospinning and vacuum evaporation deposits to form modified fibers and microporous membranes, and finally obtaining a double-layer composite fabric through hot pressing composite, solving the problems of insufficient breathability, moisture-permeability and antibacterial properties of existing clothing fabrics, achieving high breathability, good moisture-permeability and significant antibacterial effects.
Patent Information
- Application Number
- CN202411964507.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing clothing fabrics have shortcomings in breathable, moisture permeable and antibacterial properties, resulting in inadequate comfort in the clothing.
Using the production process of composite fabrics, a modified fiber and microporous membrane are deposited by mixing cotton pulp, graphene oxide solution, polyethylene, carbon nanotubes, silver-carrying antibacterial agent and moisture-permeable hot melt adhesive in a certain proportion, electrospinning and vacuum evaporation are deposited to form modified fibers and microporous membranes, and finally a double-layer composite fabric is obtained by hot pressing composite.
It achieves high breathability, good moisture permeability and significant antibacterial effect of the fabric, making the clothing more comfortable, can effectively absorb and dissipate the body's heat and sweat, while preventing bacteria from growing.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics and their production, in particular to a composite antibacterial sweat-absorbing clothing fabric, and also to a production process of the fabric. Background Art
[0002] There are many types of fabrics available, but as people's living standards improve, new types that can meet the needs of different groups of people need to be provided. People's requirements for clothing are not only about clothing style and workmanship, but more about clothing quality, which requires that clothing fabrics should keep up with the development of clothing forms. The characteristics of fabrics such as functionality, comfort, environmental protection, and health have become topics that people are paying more and more attention to.
[0003] Traditional clothing fabrics are divided into natural fibers and chemical fibers. Natural fibers are natural substances in nature, including but not limited to cotton, linen, silk, and wool, while chemical fibers are made by chemical methods, and common ones are polyester and nylon. Although natural fibers are comfortable, they are easy to wrinkle, such as cotton and linen. Silk and wool have high protein content and are prone to insects and yellowing. Chemical fiber fabrics usually have poor moisture absorption.
[0004] In summary, it is considered how to improve the air permeability, moisture permeability and antibacterial properties of clothing to make the clothing more comfortable. In view of this, we propose a composite antibacterial sweat-absorbing clothing fabric and its process. Summary of the invention
[0005] In view of the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a composite antibacterial sweat-absorbing clothing fabric and a process thereof to obtain a moisture-permeable, sweat-absorbing and antibacterial fabric.
[0006] A composite antibacterial sweat-absorbing clothing fabric comprises the following components: cotton pulp, graphene oxide solution, polyethylene, carbon nanotubes, a silver-loaded antibacterial agent and a moisture-permeable hot melt adhesive are mixed in a certain proportion to obtain the clothing fabric; wherein the ratio of the cotton pulp to the graphene oxide solution is 1 to 14:1, and the ratio of the polyethylene, carbon nanotubes and the silver-loaded antibacterial agent is 1 to 5:0.5 to 5:1.
[0007] As a further improvement of the above scheme, the mass composition of the clothing fabric is as follows: 50% to 80% cotton pulp, 6% to 50% graphene oxide solution, 4% to 10% polyethylene, 2% to 9% carbon nanotubes, 2% to 4% silver-loaded antibacterial agent, and 6% to 12% moisture-permeable hot melt adhesive.
[0008] As a further improvement of the above scheme, the moisture permeable hot melt adhesive is composed of the following parts by weight: 10 to 15 parts of polyester polyol, 3 to 6 parts of antioxidant, and 2 to 7 parts of isocyanate.
[0009] As a further improvement of the above scheme, the polyester polyol is obtained by polymerizing an acid substance and a lipid substance, and the acid substance is any one of adipic acid, carbonic acid, sebacic acid, dodecanedioic acid, terephthalic acid and isophthalic acid, and the lipid substance is any one of hexanediol, butanediol, hexanediol, diethylene glycol and neopentyl alcohol.
[0010] As a further improvement of the above scheme, the antioxidant is any one of a hindered phenol antioxidant, a phosphite antioxidant and a thioester antioxidant. In the present invention, the addition of an antioxidant makes the moisture permeable hot melt adhesive have aging resistance, thereby making the composite fabric stable to be pressed together, and the polyester polyol and isocyanate play a bonding role.
[0011] A manufacturing process of clothing fabrics, comprising the following steps:
[0012] S1 prepares graphene oxide based on a redox method, disperses the prepared graphene oxide in distilled water to obtain a graphene oxide solution for later use;
[0013] S2: mixing the graphene oxide solution and cotton pulp in proportion to obtain a spinning solution;
[0014] S3 processes the spinning solution based on electrospinning to obtain modified fibers, and the phase change fibers are processed into yarns through a spinning process, and then interwoven on a loom to form modified fiber cloth;
[0015] S4 takes polyethylene, carbon nanotubes and silver-loaded antimicrobial agent in proportion to prepare a microporous membrane;
[0016] S5 prepares moisture permeable hot melt adhesive for standby use;
[0017] S6: hot-pressing and laminating the moisture-permeable hot melt adhesive between the modified fiber cloth and the microporous membrane to obtain a composite fabric.
[0018] As a further improvement of the above scheme, the preparation of graphene oxide is specifically performed as follows:
[0019] S11: mixing sodium selenate and nickelate in proportion to obtain an acidic mixture;
[0020] S12: adding graphite powder and potassium permanganate in a ratio of 1:2 to 5 into a reaction kettle, stirring and mixing to obtain a mixture;
[0021] S13: adding the acidic mixture into the reactor, stirring and mixing the acidic mixture and the mixture to react, then adding the ice-water mixture while stirring, centrifuging and retaining the precipitate to obtain a reactant;
[0022] S14: washing, filtering and freeze-drying the reactants to obtain graphene oxide.
[0023] As a further improvement of the above scheme, the mass ratio of the sodium selenate and the nickelate is 8 to 10:1; the mass ratio of the acid mixture and the mixture is 10 to 16:1. During the reaction, the reaction temperature is 40 to 50°C, the reaction time is 12 to 15 hours, and the reaction is cooled to room temperature after completion; ice and hydrogen peroxide are mixed in a mass ratio of 100 to 140:1 to obtain the ice-water mixture, and the ice-water mixture is fully stirred after adding it until no bubbles are generated, and then centrifuged; the reactant is washed with a 10% hydrochloric acid aqueous solution, and then rinsed with pure water for 2 to 4 times. In the present invention, a 10% hydrochloric acid aqueous solution is used to remove the metal ions in the reactant, and the purpose of rinsing with pure water is to remove the acid solution remaining in the reactant.
[0024] As a further improvement of the above scheme, the specific operation of the electrospinning treatment of the spinning solution is as follows: the prepared spinning solution is subjected to electrospinning on an electrospinning machine under the spinning conditions of voltage 5-15KV, injection speed 3-4ml / h, injection distance 90-120mm, and the obtained fiber is washed, oiled and dried.
[0025] As a further improvement of the above scheme, the carbon nanotubes are prepared based on chemical vapor deposition, and the specific operation process is as follows: nickel nitrate hexahydrate is used to prepare a nickel catalyst precursor, the nickel catalyst precursor is evenly spread in a quartz boat, and then the quartz boat is placed in the constant temperature zone in the middle of the quartz reaction tube, argon is introduced into the reaction tube, and after the temperature is increased to 400-500°C at a heating rate of 10°C / min, hydrogen is introduced at 50-200mL / min for 2-4h. At this time, the nickel catalyst precursor is reduced to catalyst Ni, and the introduction of hydrogen is stopped. Then, a mixed gas is introduced into the catalyst Ni / Mg, and a catalytic cracking reaction is carried out at 450-550°C for 0.5-3h, and the introduction of methane is stopped. The furnace temperature is lowered to room temperature under an argon atmosphere to obtain product carbon nanotubes.
[0026] As a further improvement of the above scheme, the method for making the microporous membrane is specifically performed as follows:
[0027] S41: polyethylene, carbon nanotubes and silver-loaded antimicrobial agent are taken and ultrasonicated for 1 h to obtain a mixed solution for later use;
[0028] S42 heats and evaporates the mixed solution under vacuum, and the vapor is deposited in the substrate to obtain a microporous membrane. The present invention incorporates a silver-loaded antibacterial agent for sterilization and antibacterial, and utilizes the silver ions in the silver-loaded antibacterial agent to have a 100% sterilization rate for Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Aspergillus niger, and has the characteristics of good high temperature resistance and good antibacterial durability. In addition, the silver-loaded antibacterial agent has a strong adsorption and fixation effect on bacteria and molds, so that the composite fabric can effectively prevent bacteria from developing tolerance and has excellent antibacterial effect.
[0029] As a further improvement of the above scheme, the preparation method of the moisture permeable hot melt adhesive is specifically performed as follows:
[0030] S51: putting the melted polyester polyol and antioxidant into a closed reaction container, heating to 120°C, stirring at 100r / min for 10min, mixing evenly, and then evacuating to a negative pressure of 0.08-0.1MPa, and maintaining for 60min;
[0031] S52 The mixed material is cooled to 70-80°C, isocyanate is quickly added while stirring, and vacuum is drawn to a negative pressure of 0.08-0.1 MPa until the viscosity of the material is 3000-6000 cps at 90°C, then stirring is stopped to obtain a moisture permeable hot melt adhesive.
[0032] As a further improvement of the above scheme, the manufacturing process is used to manufacture the composite antibacterial and sweat-absorbing clothing fabric.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] The present invention uses graphene oxide to modify cotton fibers, and the modified fibers introduced the breathable properties of graphene oxide, which can effectively absorb and dissipate body heat and sweat, giving the human body a more comfortable experience. The microporous membrane formed by adding carbon nanotubes / silver-loaded antibacterial agents makes the fabric light and soft, and due to the microscopic network structure of carbon nanotubes, heat can be evenly and quickly dissipated to the entire fabric, and the air permeability is good, and the bactericidal effect of silver ions in the silver-loaded antibacterial agent is used to give the clothing fabric antibacterial properties.
[0035] The production process of the present invention adopts a modified fiber obtained by electrostatic spinning of a spinning stock solution formed by mixing a graphene oxide solution and cotton pulp as one layer, and adopts a microporous membrane formed by vacuum evaporation deposition of polyethylene, carbon nanotubes and silver-loaded antibacterial agents as one layer. The two layers are hot-pressed with a moisture-permeable hot melt adhesive to form a double-layer composite fabric. The clothing made of the double-layer composite fabric has advantages in moisture permeability, sweat absorption and antibacterial properties. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. Additional aspects and advantages of the present invention will be given in part in the following description, and will become apparent from the following description, or will be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0037] As used herein, the terms "comprises," "including," "contains," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0038] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range limited by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including a range of "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When a numerical range is described in this article, unless otherwise specified, the range is intended to include its end values and all integers and fractions within the range.
[0039] The specific embodiments of the present invention are described in detail below.
[0040] Example 1
[0041] This embodiment provides a composite antibacterial sweat-absorbing clothing fabric, which has the following components: cotton pulp, graphene oxide solution, polyethylene, carbon nanotubes, silver-loaded antibacterial agent and moisture-permeable hot melt adhesive are mixed in a certain proportion to obtain the clothing fabric. The ratio of the cotton pulp to the graphene oxide solution is 40:3, and the ratio of the polyethylene, carbon nanotubes and silver-loaded antibacterial agent is 2:1:1.
[0042] The clothing fabric is composed of 80% cotton pulp, 6% graphene oxide solution, 4% polyethylene, 2% carbon nanotubes, 2% silver-loaded antibacterial agent, and 6% moisture-permeable hot melt adhesive. The moisture-permeable hot melt adhesive is composed of 10 parts of polyester polyol, 3 parts of hindered phenol antioxidant, and 2 parts of isocyanate.
[0043] The manufacturing process of the clothing fabric of this embodiment includes the following steps:
[0044] S1 prepares graphene oxide based on a redox method, and the prepared graphene oxide is dispersed in distilled water to obtain a graphene oxide solution for later use.
[0045] The preparation of the graphene oxide is specifically performed as follows:
[0046] S11: Sodium selenate and nickelate are mixed in proportion to obtain an acidic mixture.
[0047] S12: Graphite powder and potassium permanganate are put into a reaction kettle in a ratio of 1:4, and stirred to mix evenly to obtain a mixture.
[0048] S13: adding the acidic mixture into the reactor, stirring and mixing the acidic mixture and the mixture to react, then adding the ice-water mixture while stirring, centrifuging and retaining the precipitate to obtain a reactant.
[0049] S14: washing, filtering and freeze-drying the reactants to obtain graphene oxide.
[0050] The mass ratio of the sodium selenate and the nickelate is 9:1; the mass ratio of the acid mixture and the mixture is 12:1. During the reaction, the reaction temperature is 45°C, the reaction time is 14 hours, and the reaction is cooled to room temperature after completion. Ice and hydrogen peroxide are mixed uniformly in a mass ratio of 120:1 to obtain the ice-water mixture, and the ice-water mixture is fully stirred after adding until no bubbles are generated, and then centrifuged. The reactant is washed with a 10% hydrochloric acid aqueous solution, and then rinsed with pure water 3 times.
[0051] S2: graphene oxide solution and cotton pulp are mixed in a ratio of 3:40 to obtain a spinning solution.
[0052] S3 treats the spinning solution based on electrospinning to obtain modified fibers, and the phase change fibers are processed into yarns through a spinning process, and then interwoven on a loom to form modified fiber cloth. The specific operation of treating the spinning solution by electrospinning is as follows: the prepared spinning solution is electrospun on an electrospinning machine, and the spinning conditions are voltage 10KV, injection speed 4ml / h, injection distance 100mm, and the obtained fibers are washed, oiled and dried.
[0053] S4 takes polyethylene, carbon nanotubes and silver-loaded antimicrobial agent in a ratio of 2:1:1 to prepare a microporous membrane.
[0054] The carbon nanotubes are prepared based on the chemical vapor deposition method, and the specific operation process is as follows: nickel nitrate hexahydrate is used to prepare a nickel catalyst precursor, the nickel catalyst precursor is evenly spread in a quartz boat, and then the quartz boat is placed in the constant temperature zone in the middle of a quartz reaction tube, argon is introduced into the reaction tube, and after the temperature is increased to 500°C at a heating rate of 10°C / min, hydrogen is introduced at 50mL / min for 2h. At this time, the nickel catalyst precursor is reduced to catalyst Ni, and the introduction of hydrogen is stopped. Then, a mixed gas is introduced into the catalyst Ni / Mg, and a catalytic cracking reaction is carried out at 450°C for 2h, and the introduction of methane is stopped. The furnace temperature is lowered to room temperature under an argon atmosphere to obtain product carbon nanotubes.
[0055] The method for making the microporous membrane is specifically performed as follows:
[0056] S41: polyethylene, carbon nanotubes and silver-loaded antimicrobial agent are taken and ultrasonicated for 1 h to obtain a mixed solution for later use;
[0057] S42: heating and evaporating the mixed solution under vacuum, and depositing the vapor in the substrate to obtain a microporous membrane.
[0058] S5: Put the melted polyester polyol and hindered phenol antioxidant into a closed reaction container, heat to 120°C, stir at 100r / min for 10min, evacuate to a negative pressure of 0.08-0.1MPa after mixing evenly, maintain for 60min, wait for the mixed material to cool to 75°C, quickly add isocyanate while stirring, and evacuate to a negative pressure of 0.1MPa until the viscosity of the material is 5000cps at 90°C, then stop stirring to obtain a moisture permeable hot melt adhesive.
[0059] S6: hot-pressing and laminating the moisture-permeable hot melt adhesive between the modified fiber cloth and the microporous membrane to obtain a composite fabric. The hot-pressing and laminating is carried out in a fabric hot press, and the hot-pressing temperature is 115° C. and the hot-pressing time is 40 seconds.
[0060] Example 2
[0061] This embodiment provides a composite antibacterial sweat-absorbing clothing fabric, which has the following components: cotton pulp, graphene oxide solution, polyethylene, carbon nanotubes, silver-loaded antibacterial agent and moisture-permeable hot melt adhesive are mixed in a certain proportion to obtain the clothing fabric. The ratio of the cotton pulp to the graphene oxide solution is 2.4:1, and the ratio of the polyethylene, carbon nanotubes and silver-loaded antibacterial agent is 1.25:1.25:1.
[0062] The clothing fabric is composed of 55% cotton pulp, 25% graphene oxide solution, 5% polyethylene, 5% carbon nanotubes, 4% silver-loaded antibacterial agent, and 6% moisture-permeable hot melt adhesive. The moisture-permeable hot melt adhesive is composed of 12 parts polyester polyol, 4 parts antioxidant, and 5 parts isocyanate.
[0063] The manufacturing process of the clothing fabric of this embodiment is the same as that of Embodiment 1, except that the mixing ratios of the components in the clothing fabric are different, which will not be described in detail here.
[0064] Example 3
[0065] The present embodiment provides a composite antibacterial and sweat-absorbing clothing fabric, which has the following components: cotton pulp, graphene oxide solution, polyethylene, carbon nanotubes, silver-loaded antibacterial agent and moisture-permeable hot melt adhesive are mixed in a certain proportion to obtain the clothing fabric. Among them, the ratio of the cotton pulp and the graphene oxide solution is 5:3, and the ratio of the polyethylene, carbon nanotubes and the silver-loaded antibacterial agent is 1.25:1:1.
[0066] The clothing fabric is composed of 50% cotton pulp, 30% graphene oxide solution, 5% polyethylene, 4% carbon nanotubes, 4% silver-loaded antibacterial agent, and 7% moisture-permeable hot melt adhesive. The moisture-permeable hot melt adhesive is composed of 15 parts of polyester polyol, 6 parts of antioxidant, and 7 parts of isocyanate.
[0067] The manufacturing process of the clothing fabric of this embodiment is the same as that of Embodiment 1, except that the mixing ratios of the components in the clothing fabric are different, which will not be described in detail here.
[0068] Example 4
[0069] The difference between this embodiment and embodiment 2 is that in this embodiment, no graphene oxide solution is added, and the rest is the same as embodiment 2.
[0070] The fabrics of Examples 1-4 are tested for moisture permeability. The moisture permeability test is: the mass of water vapor that passes vertically through a unit area of a sample within a specified time under specified temperature and humidity conditions on both sides of the sample. The specific test method refers to ASTM E96. The test results are: the moisture permeability of the fabric of Example 1 is 87%, the moisture permeability of the fabric of Example 2 is 90%, the moisture permeability of the fabric of Example 3 is 88%, and the moisture permeability of the fabric of Example 4 is 72%. The above test results prove that the introduction of graphene oxide in the present invention significantly improves the moisture permeability of the fabric obtained. Therefore, the fabric of the present invention has good air permeability and moisture permeability, can effectively absorb and dissipate body heat and sweat, and give the human body a more comfortable experience.
[0071] The above embodiments are merely preferred implementations of the present invention. Any simple modification, amendment and substitution of the above embodiments based on the technical essence of the present invention shall fall within the scope of the technical solution of the present invention.
Claims
1. A composite antibacterial sweat-absorbing clothing fabric, characterized in that: The clothing fabric has the following components: The clothing fabric is prepared by mixing cotton pulp, graphene oxide solution, polyethylene, carbon nanotubes, silver-loaded antibacterial agent and moisture-permeable hot melt adhesive in a certain proportion; wherein the ratio of the cotton pulp to the graphene oxide solution is 1-14:1, and the ratio of the polyethylene, carbon nanotubes and silver-loaded antibacterial agent is 1-5:0.5-5:
1.
2. The composite antibacterial sweat-absorbing clothing fabric according to claim 1, characterized in that: The clothing fabric is composed of 50% to 80% cotton pulp, 6% to 50% graphene oxide solution, 4% to 10% polyethylene, 2% to 9% carbon nanotubes, 2% to 4% silver-loaded antibacterial agent, and 6% to 12% moisture-permeable hot melt adhesive.
3. The composite antibacterial sweat-absorbing clothing fabric according to claim 1, characterized in that: The moisture permeable hot melt adhesive is composed of the following parts by weight: 10-15 parts of polyester polyol, 3-6 parts of antioxidant, and 2-7 parts of isocyanate.
4. The composite antibacterial sweat-absorbing clothing fabric according to claim 3, characterized in that: The polyester polyol is obtained by polymerizing an acidic substance and a lipidic substance, wherein the acidic substance is any one of adipic acid, carbonic acid, sebacic acid, dodecanedioic acid, terephthalic acid and isophthalic acid, and the lipidic substance is any one of hexanediol, butanediol, hexanediol, diethylene glycol and neopentyl alcohol; The antioxidant is any one of hindered phenol antioxidants, phosphite antioxidants and thioester antioxidants.
5. A process for producing clothing fabrics, characterized in that: The following steps are involved: S1 prepares graphene oxide based on a redox method, disperses the prepared graphene oxide in distilled water to obtain a graphene oxide solution for later use; S2: mixing the graphene oxide solution and cotton pulp in proportion to obtain a spinning solution; S3 processes the spinning solution based on electrospinning to obtain modified fibers, and the phase change fibers are processed into yarns through a spinning process, and then interwoven on a loom to form modified fiber cloth; S4 takes polyethylene, carbon nanotubes and silver-loaded antimicrobial agent in proportion to prepare a microporous membrane; S5 prepares moisture permeable hot melt adhesive for standby use; S6: hot-pressing and laminating the moisture-permeable hot melt adhesive between the modified fiber cloth and the microporous membrane to obtain a composite fabric.
6. The textile fabric manufacturing process according to claim 5, characterized in that: The preparation of the graphene oxide is specifically performed as follows: S11: mixing sodium selenate and nickelate in proportion to obtain an acidic mixture; S12: adding graphite powder and potassium permanganate in a ratio of 1:2 to 5 into a reaction kettle, stirring and mixing to obtain a mixture; S13: adding the acid mixture into the reactor, stirring and mixing the acid mixture and the mixture to react, then adding the ice-water mixture while stirring, centrifuging and retaining the precipitate to obtain a reactant; S14: washing, filtering, and freeze-drying the reactants to obtain graphene oxide; The mass ratio of the sodium selenate and the nickelate is 8-10:1; the mass ratio of the acid mixture and the mixture is 10-16:1; during the reaction, the reaction temperature is 40-50°C, the reaction time is 12-15h, and the reaction is cooled to room temperature after completion; ice and hydrogen peroxide are mixed uniformly at a mass ratio of 100-140:1 to obtain the ice-water mixture, and the ice-water mixture is fully stirred after being added until no bubbles are generated, and then centrifuged; the reactants are washed with a 10% hydrochloric acid aqueous solution, and then rinsed with pure water 2-4 times.
7. The manufacturing process according to claim 6, characterized in that: The specific operation of the electrospinning treatment of the spinning solution is as follows: the prepared spinning solution is electrospun on an electrospinning machine under the spinning conditions of 5-15KV voltage, 3-4ml / h jet speed, 90-120mm jet distance, and the obtained fiber is washed, oiled and dried; The carbon nanotubes are prepared based on a chemical vapor deposition method, and the specific operation process is as follows: nickel nitrate hexahydrate is used to prepare a nickel catalyst precursor, the nickel catalyst precursor is evenly spread in a quartz boat, and then the quartz boat is placed in a constant temperature zone in the middle of a quartz reaction tube, argon is introduced into the reaction tube, and after the temperature is raised to 400-500°C at a heating rate of 10°C / min, hydrogen is introduced at 50-200mL / min for 2-4h, at which time the nickel catalyst precursor is reduced to catalyst Ni, the introduction of hydrogen is stopped, and then a mixed gas is introduced into the catalyst Ni / Mg, and a catalytic cracking reaction is carried out at 450-550°C for 0.5-3h, and the introduction of methane is stopped, and the furnace temperature is lowered to room temperature under an argon atmosphere to obtain product carbon nanotubes.
8. The manufacturing process according to claim 7, characterized in that: The method for making the microporous membrane is specifically performed as follows: S41 takes polyethylene, carbon nanotubes and silver-loaded antimicrobial agent, and ultrasonicates them for 1 h to obtain a mixed solution for later use; S42: heating and evaporating the mixed solution under vacuum, and depositing the vapor in the substrate to obtain a microporous membrane.
9. The manufacturing process according to claim 8, characterized in that: The preparation method of the moisture permeable hot melt adhesive is specifically performed as follows: S51: putting the melted polyester polyol and antioxidant into a closed reaction container, heating to 120°C, stirring at 100 r / min for 10 min, and after mixing evenly, evacuating to a negative pressure of 0.08-0.1 MPa, and maintaining for 60 min; S52: The mixed material is cooled to 70-80°C, isocyanate is quickly added while stirring, and vacuum is drawn to a negative pressure of 0.08-0.1 MPa until the viscosity of the material is 3000-6000 cps at 90°C, then stirring is stopped to obtain a moisture permeable hot melt adhesive.
10. The manufacturing process according to claim 9, characterized in that: The production process is used to produce the composite antibacterial and sweat-absorbing clothing fabric as described in any one of claims 1 to 4.